1999
DOI: 10.1172/jci7094
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen decreases TNF gene expression by blocking JNK activity and the resulting production of c-Jun and JunD

Abstract: Central to the bone-sparing effect of estrogen (E 2 ) is its ability to block the monocytic production of the osteoclastogenic cytokine TNF-α (TNF). However, the mechanism by which E 2 downregulates TNF production is presently unknown. Transient transfection studies in HeLa cells, an E 2 receptor-negative line, suggest that E 2 inhibits TNF gene expression through an effect mediated by estrogen receptor β (ERβ). We also report that in RAW 264.7 cells, an E 2 receptor-positive murine monocytic line, E 2 downreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
142
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(159 citation statements)
references
References 67 publications
14
142
2
1
Order By: Relevance
“…Downregulation of JNK by estrogen decreases JunD phosphorylation, which in turn decreases expression of the junD mRNA. These observations indicate that phosphorylation is necessary for JunD transcriptional transactivation of the junD promoter and that JNK stimulates the autoregulatory loop that modulates junD expression (Srivastava et al, 1999). Although the 43 Nterminal residues of JunD do not bind JNK (and do not promote ubiquitination, as discussed above), residues 49-59 of JunD provide a low-affinity docking domain for JNK that is necessary for phosphorylation (Figure 1, efficient phosphorylation is designated by the red squares labeled Pi) (Kallunki et al, 1996;Fuchs et al, 1997;Yazgan and Pfarr, 2002).…”
Section: Post-translational Modification and Alternative Protein-protmentioning
confidence: 90%
“…Downregulation of JNK by estrogen decreases JunD phosphorylation, which in turn decreases expression of the junD mRNA. These observations indicate that phosphorylation is necessary for JunD transcriptional transactivation of the junD promoter and that JNK stimulates the autoregulatory loop that modulates junD expression (Srivastava et al, 1999). Although the 43 Nterminal residues of JunD do not bind JNK (and do not promote ubiquitination, as discussed above), residues 49-59 of JunD provide a low-affinity docking domain for JNK that is necessary for phosphorylation (Figure 1, efficient phosphorylation is designated by the red squares labeled Pi) (Kallunki et al, 1996;Fuchs et al, 1997;Yazgan and Pfarr, 2002).…”
Section: Post-translational Modification and Alternative Protein-protmentioning
confidence: 90%
“…34 In addition, several reports showed that estrogen is known to inhibit TNF-a activity and reduced estrogen levels in post-menopausal women predispose to a higher incidence of aneurysm development. [35][36][37][38] Interestingly, there were reports showing that significant differences in the levels of TNF-a production when females and males stimulated under certain physiological condition, such as psychological stress and early alcohol-induced liver injury. 39,40 In our study, the risk allele of rs1799724 (À857T) are known to have a significantly higher level of TNF-a production from concanavalin Aactivated peripheral blood mononuclear cells, 41 implying the importance of this variant in IA development, particularly in female IA.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen supplementation also reduces TNFa levels in cells of monocyte/macrophage lineage through involving the non-ERE transcription factor AP-1. Surprisingly, ERb rather than ERa plays the key role in this effect (20). In addition, estrogen acting through ERa modulates the postreceptor TNFa effects through NF-kB inhibition and consequently reduces adhesion molecule expression and leukocyte recruitment in endothelial cells (21).…”
Section: Estrogen and Tumor Necrosis Factormentioning
confidence: 99%